FEATURES OF ISLAMIC INHERITANCE LAW - Khafiza Khamidovna Musaeva. (Scholar Express Journals, 2023)
In this article, the authors explore the features of the regulation of inheritance relationships in Islamic law. The aim of the study is to determine the queue inheritance and differences in inheritance, bequest and the Shariah. Highlights the importance of Sharia law as an essential source of inheritance law for Muslims. Keywords: inheritance, Muslim law, wills, the heirs of the Shariah. Abstract: in this article, the authors explore the features of the regulation of inheritance relationships in Islamic law. The aim of the study is to determine the queue inheritance and differences in inheritance, bequest and the Shariah. Highlights the importance of Sharia law as an essential source of inheritance law for Muslims
Keywords: inheritance; Muslim law; wills; Shariah